(untitled) (World Economics and Finance Bulletin, 2023)
In this article, the problems and solutions of food safety will be discussed. In fact, there are about 10,000 food industry enterprises operating in our country today, and their share in the gross domestic product is more than 16 percent (%). By safe food, we usually mean high-quality, environmentally friendly, genetically modified organism (GMO)-free products that do not contain harmful food-related elements such as pesticides. In order to monitor the quality of food products, establish quality control of food products using a scanning system. step by step adjustment.